Pengaruh Literasi Keuangan, Heuristic Bias, Framing Effect, Cognitive Illusions dan Herd Mentality Terhadap Keputusan Investasi Kripto: Studi pada Komunitas Kripto di Indonesia - Evan Colin Colin; Adrie Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The purpose of this study is to analyze and provide evidence regarding the influence of financial literacy, heuristic bias, framing effect, cognitive illusions, and herd mentality on crypto investment decisions among crypto investors in Indonesia. Data were obtained from respondents who are crypto investors within the Indonesian crypto community, using a convenience sampling technique. Data were analyzed using descriptive statistics and multiple linear regression models using SPSS software. Testing was carried out through validity and reliability tests, classical assumption tests, and simultaneous and partial hypothesis tests. The results show that financial literacy, heuristic bias, framing effect, cognitive illusions, and herd mentality simultaneously have a significant influence on crypto investment decisions. Partially, these five variables also have a positive and significant influence on crypto investment decisions. These findings contribute to investors' understanding of the importance of improving financial literacy and the ability to manage psychological influences to make investment decisions more rational and measurable. Theoretically, this study supports behavioral finance theory, which explains that investment decisions are influenced by psychological and social factors, and the Theory of Planned Behavior, which emphasizes the role of knowledge in shaping attitudes and behavioral control that influence investment decisions.